Antibacterial and Antifungal Activity of Heartwood of Acacia catechu of Nepal - Joshi, Susan; Subedi, Yagya Prasad; Paudel, Shobha Kumari (Journal of Nepal Chemical Society, 2012)
Antibacterial activity of different extracts of heartwood of Acacia catechu were tested against 11 species of bacteria and antifungal activity were tested against four species of fungi. Among bacteria species highest zone of inhibition (ZOI) was measured against Pseudomonas species by diethyl ether extract, likewise among fungal organism highest zone of inhibition (ZOI) was measured against Fusarium oxysporim by ethyl acetate extract. No extracts showed activity against Salmonella typhi, Salmonella paratyphi, Escherichia coli and Proteus mirabilis. The minimum bactericidal concentration (MBC) of ethyl acetate extract was evaluated against Bacillus subtilis, Klebsiella pneumonia, Staphylococus aureus and Shigella species. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6667 J. Nepal Chem. Soc., Vol. 27, 2011 94-99